Marketing Strategy for Non-Performing Loan Collateral through Auction at PT Bank X (Persero) Tbk - Rafi Athallah Primaditya; Albari (Cita konsultindo, 2025)
This study aims to analyze the marketing strategies applied by PT Bank X (Persero) Tbk in selling non-performing loan (NPL) collateral assets through auction mechanisms. The research adopts a qualitative method with a narrative approach, using in-depth interviews with three key informants from the bank’s Special Asset Management Unit (RSAM). The results show that offline marketing remains the dominant strategy due to its higher effectiveness in building trust with prospective buyers. Digital promotion via platforms such as WhatsApp, Instagram, OLX, and Rumah123 serves as a supplementary tool to raise awareness and expand audience reach. However, the marketing process faces several challenges, including non-strategic asset locations, third-party occupancy, and incomplete legal documents. In addition, the limitations of digital infrastructure and trust issues in online transactions are also significant. This research contributes to understanding practical marketing strategies for problem assets in the banking sector and provides strategic recommendations to optimize sales efforts through a combination of integrated offline and digital approaches.